Comparison of motives underlying food choice and barriers to healthy eating among low medium income consumers in Uruguay - Gastón Ares; Leandro Machín; Alejandra Girona; María Rosa Curutchet; Ana Giménez
Abstract: Interventions aimed at changing dietary patterns should be designed based on the main motives underlying the food choices of specific target populations. The aim of the present study was to identify motives underlying food choice and barriers to healthy eating among consumers in two socioeconomic levels in Uruguay. Eleven focus groups were carried out with a total of 76 participants. Six of the groups involved low income participants and the others were conducted with middle income participants. Discussions were held around frequently consumed products, motives underlying food choices and barriers to healthy eating. Results confirmed the strong influence of income level on motives underlying food choice and barriers to the adoption of healthy eating. Low income participants described their choices as mainly driven by economic factors and satiety, whereas convenience was the main determinant of food selection for middle income participants. Implications for the design of public policies targeted at each group are discussed.